2020
DOI: 10.1016/j.bjpt.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of isokinetic peak torque and muscular power on the functional performance of active and inactive community-dwelling elderly: a cross-sectional study

Abstract: Objective: To verify the importance of the isokinetic muscular torque and power of knee extensors and flexors on the functional performance of active and inactive elderly women. Methods: A cross-sectional observational study was conducted with 116 community-dwelling women (≥60 years old) without severe cognitive and/or motor dysfunction. Isokinetic muscle function was measured by peak torque and muscle power at 60 • /s (5 repetitions) and 180 • /s (15 repetitions), respectively. Mobility was evaluated by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…For example, it has been estimated that a mere 1% improvement in performance can double the odds of victory for an elite athlete [65]; in this context a 5% increase is enormous. Similarly, based on data from de Moura et al [66] a 5% increase in maximal knee extensor power would be expected to reduce the odds of limitations in dynamic balance, habitual gait speed, or chair stand performance in inactive elderly subjects by roughly one-third. Thus, it is clear that dietary NO 3 − holds considerable potential as a means of enhancing muscular power in both athletic and patient populations alike.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been estimated that a mere 1% improvement in performance can double the odds of victory for an elite athlete [65]; in this context a 5% increase is enormous. Similarly, based on data from de Moura et al [66] a 5% increase in maximal knee extensor power would be expected to reduce the odds of limitations in dynamic balance, habitual gait speed, or chair stand performance in inactive elderly subjects by roughly one-third. Thus, it is clear that dietary NO 3 − holds considerable potential as a means of enhancing muscular power in both athletic and patient populations alike.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mild-AD group had acceptable SEM% and MDC 95 % for average peak torque of the knee flexors, which was not found in the moderate-AD group. Reliable isokinetic measures for the evaluation of knee flexors in older adults with AD is important, as isokinetic variables of knee flexor muscle strength have been found to be associated with mobility and lower limb muscle strength in healthy older adults [ 11 ]. In contrast, the analysis of the maintenance of maximum strength (total work) revealed that the knee extensors had the best absolute reliability values.…”
Section: Discussionmentioning
confidence: 99%
“…The adaptation and standardization of the isokinetic evaluations were ensured with communication strategies adopted for the participants with AD, such as maintaining eye contact when speaking, speaking slowly and clearly, explaining the actions prior to their execution as well as repeating the explanation of the correct execution and demonstrating the tests. Prior to the isokinetic evaluations on D1 and D2, an explanation was given and the tests were demonstrated on the non-dominant lower limb, followed by familiarization on the dominant lower limb for each test and angular velocity with three submaximal repetitions and one maximum repetition [ 9 – 11 ]. After familiarization, the main examiner asked the participants if they understood the execution of the tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, angle of peak torque is an important measure of muscle function because it represents the optimal point of torque and angular displacement, showing the interaction between length and tension relationship and changes in the angle of insertion [1,9]. Lastly, average power is related to dynamic balance, mobility and lower limb function [26].…”
Section: Discussionmentioning
confidence: 99%